Maintenance Management Strategy at Faringa Laundry: Improving Efficiency and Reliability - Anashrullah; Nilam Sari, Meci (Pt. Threeple Herphi Educate, 2024)
Faringa Laundry is a laundry service business that has been operating since 2018 and is known for its quality service. This research analyzes maintenance reliability management at Faringa Laundry to identify the maintenance strategies implemented, factors that affect equipment reliability, and metrics used to assess reliability. The analysis was conducted on key assets that require maintenance, such as washing machines, steam irons, and dryers. This research uses MTBF (Mean Time Between Failures) and MTTR (Mean Time To Repair) metrics to measure reliability and repair efficiency. The results show that Faringa Laundry implements a corrective maintenance strategy, where repair actions are taken only after a breakdown occurs. This study recommends implementing a more structured preventive maintenance strategy to improve equipment reliability and longevity and reduce the frequency and cost of repairs.